Mayas, spirituality, and the unfinished history of conflict in Guatemala. - Hinojosa, Servando Z. (Revista cultura y religión, 2011)
Maya spiritual practice in Guatemala has been actively challenged by mainstream religions and by pressures originating from other institutions. Many Maya ritualists have been directly reproached by religious leaders and have been targeted by a state apparatus that associates rural Maya life with insurgency. As a result, many Maya spiritual elements have been pushed to, and kept at, the margins of society. Focusing on the past two decades, this essay reviews how Mayas nevertheless maintain an active ritual life. They do this by engaging in a close relationship with the spirit-owners of the landscape, beings upon whom humans depend for their sustenance and life. They do this, also, in the face of many challenges from organized religions, the educational system, and the military. Having considered the effects of these institutions upon Maya spirituality, I then put forward some concerns Mayas face when addressing how to value and promote Maya spiritual practices in Guatemala. In addition to encouraging young Mayas to uphold their heritage, Mayas may need to prevail upon Catholic and evangelical Protestant congregations to suspend judgment about Maya spirituality and to acknowledge its far-reaching importance in culturally pluralistic society.